2011
DOI: 10.4103/0970-9290.93449
|View full text |Cite
|
Sign up to set email alerts
|

Survival of dental implants in native and grafted bone in irradiated head and neck cancer patients: A retrospective analysis

Abstract: There was no significant difference in survival when implants were placed in native or grafted bone in irradiated head and neck cancer patients. For implants placed in native bone, survival was significantly influenced by the location of the implant (maxilla or mandible, anterior or posterior).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…more delayed failures [15][16][17]. Dose distribution in the different part of the bone can obviously explain these differences.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…more delayed failures [15][16][17]. Dose distribution in the different part of the bone can obviously explain these differences.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Granstrom et al (1994) found an increased rate of implant loss in irradiated subjects compared with nonirradiated ones. Conversely, Buddula et al (2011) reported high success rates of implants placed in grafted (98.1%) and native (100.0%) mandibular bones over a 3-year period. Moreover, 2 publications using animal models have shown that implant stability during osseointegration may be impaired in irradiated jaws because of the decrease in bone vascularity and vitality (Verdonck et al, 2008b); however, in the short term, the bone mineral density seems to be similar to that of nonirradiated alveolar bone (Verdonck et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…[51314151617] Animal experimentation models also show rate of failure of dental implants under similar conditions. [181920] In the present scenario, there are no strict criteria about the success or failure of dental implants in irradiated jaws of cancer treated patients, therefore, we evaluated retrospectively, the clinical outcome of dental implants in a series of patients.…”
Section: Discussionmentioning
confidence: 99%